2021
DOI: 10.1016/j.xfre.2021.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Dual trigger protocol is an effective in vitro fertilization strategy in both normal and high responders without compromising pregnancy outcomes in fresh cycles

Abstract: Objective: To study the birth rates of normal vs. high responders after dual trigger of final oocyte maturation with gonadotropinreleasing hormone (GnRH) agonist and human chorionic gonadotropin in fresh in vitro fertilization (IVF) cycles in which ovarian stimulation was achieved by a flexible GnRH antagonist protocol. Design: Retrospective cohort study. Setting: University hospital. Patient(s): In women <35 years of age, 290 fresh IVF cycles using the dual trigger protocol with day 5 embryo transfers from Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Chung RK supports dual trigger protocol as an effective in vitro fertilization strategy for high responders without compromising pregnancy outcomes in fresh cycles [22]. And Li S' study demonstrated that dual trigger is capable of preventing severe OHSS while still maintaining an excellent high quality embryo rate in high ovarian responders of GnRH-ant protocols [23].…”
Section: Discussionmentioning
confidence: 92%
“…Chung RK supports dual trigger protocol as an effective in vitro fertilization strategy for high responders without compromising pregnancy outcomes in fresh cycles [22]. And Li S' study demonstrated that dual trigger is capable of preventing severe OHSS while still maintaining an excellent high quality embryo rate in high ovarian responders of GnRH-ant protocols [23].…”
Section: Discussionmentioning
confidence: 92%
“…Another retrospective analysis by Li et al [39] examined the use of dual trigger using triptorelin and low dose HCG (2000 u) for high responders which included PCOS (37% of the population). The dual trigger was compared to standard HCG dose (10 000 u) and low dose HCG (8000 u).…”
Section: Trigger Of Final Follicular Maturationmentioning
confidence: 99%
“…One alternative approach is the use of GnRH agonist in combination with low dose of hCG for to allow for CL support via hCG but also reduce risk of OHSS compared to a standard dose hCG trigger. This was examined in a retrospective study of 290 fresh IVF cycles by Chung et al [39]. They compared outcomes after IVF/ICSI with 40 mg leuprolide and 1500 IU hCG in normal responders with <30 oocytes retrieved (215 cycles) and high responders with !30 oocytes retrieved (75 cycles).…”
Section: Trigger Of Final Follicular Maturationmentioning
confidence: 99%